COVID-19 quarantine measures are associated with negative social impacts and compromised follow-up care in patients with inflammatory bowel disease in Brazil - Feitosa, Marley Ribeiro (Ann Gastroenterol, 2021)
BACKGROUND: COVID-19 has affected the entire world. We aimed to determine the impact of COVID-19 containment measures on the daily life and follow up of patients with inflammatory bowel disease (IBD). METHODS: During May 2020, we evaluated 179 (79.6%) patients with Crohn’s disease (CD) and 46 (20.4%) with ulcerative colitis (UC) by telephone, using a structured questionnaire to gather information on social impact and IBD follow up. RESULTS: Some kind of social distancing measure was reported by 95.6% of our patients, self-quarantine (64.9%) being the most frequent. Depressive mood was the most prevalent social impact (80.2%), followed by anxiety/fear of death (58.2%), insomnia (51.4%), daily activity impairment (48%), sexual dysfunction (46.2%), and productivity impairment (44%). The results were similar when we compared patients with active disease to those in remission and patients with UC to those with CD. Analysis of IBD follow up showed that 83.1% of all patients missed an IBD medical appointment, 45.5% of the patients missed laboratory tests, 41.3% missed the national flu vaccination program, 31.3% missed any radiologic exam, 17.3% missed colonoscopy, and 16.9% failed to obtain biologic therapy prescriptions. Biologics were discontinued by 28.4% of the patients. UC patients had higher rates of missed vaccination than CD patients (56.5% vs. 37.4%, P=0.02) and more failures to obtain a biologic prescription (28.3% vs. 14.0%, P=0.02). CONCLUSIONS: Our study reveals alarming social impacts and declining follow-up care for IBD patients during the COVID-19 outbreak. These findings may have implications for disease control in the near future.